On Noncooperative Capital Income Taxation in Open Economies - Kletzer, Kenneth (International Monetary Fund, 1990)
This paper discusses the strategic use of capital income taxation and lump-sum fiscal policies for gaining national advantage in an integrated world capital market. Each fiscal authority seeks to maximize a social welfare function defined over the utilities of home country residents incorporating national redistributing objectives. A national optimum policy is to impose a non-discriminatory source-based capital income tax or subsidy along with an optimal lump-sum tax and transfer plan. Residence-based capital income taxes do not augment the set of lump-sum fiscal instruments, although both policies can be used to influence the world interest rate to national advantage, redistributing welfare internationally. When unrestricted lump-sum fiscal policies are unavailable, source-based capital income taxes may be needed to achieve distributional objectives, so that departures from global production efficiency can arise in a cooperative equilibrium